Waktu Pulih Sadar Pasien Pasca General Anestesi - Nabila Nada Fauziyyah; Tophan Heri Wibowo; Septian Mixrova Sebayang (Khatulistiwa Nursing Journal, 2025)
Background: Recovery of consciousness is an important indicator of successful outcomes following general anesthesia. Delays in regaining consciousness may lead to complications such as airway obstruction and neurological disorders. Objective: To determine the duration of consciousness recovery in patients after general anesthesia at RSUD Dr. Soedirman Kebumen. Method: A descriptive quantitative study with a cross-sectional design involving 60 patients selected through consecutive sampling. The instrument used was an observation sheet based on the Aldrete Score. Data were analyzed using a univariate approach and presented through frequency distribution and descriptive statistics. Result: The majority of respondents were adults (74.2%), female (53.2%), and had an ASA physical status of II (77.4%). The average recovery time was 11.43 minutes, ranging from 6 to 23 minutes. Conclusion: Most patients regained consciousness within a normal time range following general anesthesia.